Direct C(sp3)–H Activation of Carboxylic Acids - Uttry, Alexander; van Gemmeren, Manuel (Synthesis, 2020)
Carboxylic acids are important in a variety of research fields and applications. As a result, substantial efforts have been directed towards the C–H functionalization of such compounds. While the use of the carboxylic acid moiety as a native directing group for C(sp2)–H functionalization reactions is well established, as yet there is no general solution for the C(sp3)–H activation of aliphatic carboxylic acids and most endeavors have instead relied on the introduction of stronger directing groups. Recently however, novel ligands, tools, and strategies have emerged, which enable the use of free aliphatic carboxylic acids in C–H-activation-based transformations.1 Introduction2 Challenges in the C(sp3)–H Bond Activation of Carboxylic Acids3 The Lactonization of Aliphatic Carboxylic Acids4 The Directing Group Approach5 The Direct C–H Arylation of Aliphatic Carboxylic Acids6 The Direct C–H Olefination of Aliphatic Carboxylic Acids7 The Direct C–H Acetoxylation of Aliphatic Carboxylic Acids8 Summary
Keywords: carboxylic acids; C–H activation; native directing group; synthetic methodology